2013
DOI: 10.1021/mz4003744
|View full text |Cite
|
Sign up to set email alerts
|

Endowing Single-Chain Polymer Nanoparticles with Enzyme-Mimetic Activity

Abstract: ABSTRACT:The development of simple, efficient and robust strategies affording the facile construction of biomimetic organocatalytic nano-objects is currently a subject of great interest. Herein, a new pathway to artificial organocatalysts based on partially collapsed individual soft nano-objects displaying useful and diverse biomimetic catalytic functions is reported. Single-chain polymer nanoparticles endowed with enzyme-mimetic activity synthesized following this new route display: i) a relatively extended m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
192
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 138 publications
(197 citation statements)
references
References 39 publications
5
192
0
Order By: Relevance
“…Among the various techniques employed to these ends, the collapse of single polymer chains (precursors) via purely intramolecular cross-linking, into single-chain nanoparticles (SCNPs), has gained increasing interest over recent years [2][3][4][5] . Significant effort is being devoted to endow SCNPs with useful functions for multiple applications in, e.g., nanomedicine, biosensing, bioimaging or catalysis [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various techniques employed to these ends, the collapse of single polymer chains (precursors) via purely intramolecular cross-linking, into single-chain nanoparticles (SCNPs), has gained increasing interest over recent years [2][3][4][5] . Significant effort is being devoted to endow SCNPs with useful functions for multiple applications in, e.g., nanomedicine, biosensing, bioimaging or catalysis [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations by experiments and simulations have highlighted that, in general, the usual synthesis protocols in good solvent conditions produce SCNPs with open, sparse conformations 8,9,11,12 . As revealed by extensive simulations 11 , this feature originates from a fundamental property: the self-avoiding conformations of the linear precursors in good solvent.…”
Section: Introductionmentioning
confidence: 99%
“…We 7 and others 8,9 have demonstrated that catalytic properties can be imparted to singlechain nanoparticles through polymer folding/collapse accompanied by efficient catalyst immobilization. The potential use of single-chain nanoparticles as drug / siRNA nanocarriers and photostable bioimaging agents relies on the improved construction of functional folded/collapsed single polymer chains.…”
mentioning
confidence: 99%
“…SCNPs are obtained, generally at highly diluted conditions, through purely intramolecular cross-linking of single polymer precursors. A series of investigations by small-angle neutron (SANS) and X-ray scattering (SAXS) [8,13,19,20] have revealed that SCNPs synthesized through coventional routes are usually sparse objects with open topologies. A compilation of literature results for SCNPs in solution with very different chemical structures [21] reveals scaling behavior, R ∼ N ν , of the macromolecular radius R with the polymerization degree N, with an average exponent ν ≈ 0.5.…”
Section: Introductionmentioning
confidence: 99%